Extrinsic factors that influence employee loyalty at Brahim’s sats foodservices / Ainaa Hazirah Che Mud and Siti Nabilah Hani Jamaluddin - Che Mud, Ainaa Hazirah; Jamaluddin, Siti Nabilah Hani (2018)
This research aimed to study the extrinsic factors that affect employees to have loyalty to an organization. The researcher assumed that satisfaction in their job can create loyalty. The study also aimed to determine what expectations of employees are in order to earn their loyalty to the organization. A questionnaire has been use as the instrument in this study. The Statistical Package for Social Sciences (SPSS) program version 23.0 was used to analyze the data. Descriptive statistics in terms of percentage, mean and standard deviation were applied to analyze the data. The findings of the study indicated that factors like nature of work, career advancement and recognition, employment benefits, relationship with their supervisors and colleagues and working environment all have an effect on employees loyalty to the organization. The principle recommendation for further research is other factors, which have an effect on organizational loyalty, such as personality, punctuality, emotional equivalence, social support and others. All these should be considered to see whether or not there is any relationship between them.